Angiotensin-converting enzyme 2: a double-edged sword in COVID-19 patients with an increased risk of heart failure - Razeghian-Jahromi, Iman; Zibaeenezhad, Mohammad Javad; Lu, Zhibing; Zahra, Elyaspour; Mahboobeh, Razmkhah; Lionetti, Vicenzo (Heart failure reviews, 2021)
The coronavirus disease (COVID-19) pandemic is a global health priority. Given that cardiovascular diseases (CVD) are the leading cause of morbidity around the world and that several trials have reported severe cardiovascular damage in patients infected with SARS-CoV-2, a substantial number of COVID-19 patients with underlying cardiovascular diseases need to continue their medications in order to improve myocardial contractility and to prevent the onset of major adverse cardiovascular events (MACEs), including heart failure. Some of the current life-saving medications may actually simultaneously expose patients to a higher risk of severe COVID-19. Angiotensin-converting enzyme 2 (ACE2), a key counter regulator of the renin-angiotensin system (RAS), is the main entry gate of SARS-CoV-2 into human host cells and an established drug target to prevent heart failure. In fact, ACE inhibitors, angiotensin II receptor blockers, and mineralocorticoid antagonists may augment ACE2 levels to protect organs from angiotensin II overload. Elevated ACE2 expression on the host cell surface might facilitate viral entrance, at the same time sudden nonadherence to these medications triggers MACEs. Hence, safety issues in the use of RAS inhibitors in COVID-19 patients with cardiac dysfunction remain an unsolved dilemma and need paramount attention. Although ACE2 generally plays an adaptive role in both healthy subjects and patients with systolic and/or diastolic dysfunction, we conducted a literature appraisal on its maladaptive role. Understanding the exact role of ACE2 in COVID-19 patients at risk of heart failure is needed to safely manage RAS inhibitors in frail and non-frail critically ill patients.